OPEN UNEMPLOYMENT RATE AND ITS IMPLICATIONS ON POVERTY IN DKI JAKARTA PROVINCE - Fajarini, Anisa; Rozali, Muhammad; Rambe, Joonner (Berajah Journal, 2024)
This research aims to analyze the impact of the Provincial Minimum Wage (UMP), formal and informal sector human resource absorption on the Open Unemployment Rate (TPT) and its implications for poverty levels in DKI Jakarta Province. Low education and income levels contribute to poverty by affecting the quality of human resources. The study uses Classical Assumption Tests, Heteroscedasticity Tests, and multiple regression analyses. Results indicate that the UMP significantly and positively affects poverty levels. The significance value for the informal sector's human resource absorption (X2) is 0.0016, confirming its significant positive correlation with the TPT. Similarly, the TPT has a positive and significant influence on poverty, with a significance value of 0.006. The regression analysis shows that UMP and human resource absorption from both formal and informal sectors together have a significant positive effect on the TPT, with a p-value of 0.000. Thus, the UMP, formal, and informal sector human resources significantly influence open unemployment, which in turn affects poverty levels in DKI Jakarta Province. These findings highlight the interconnectedness of wage policies, employment sectors, and poverty, underscoring the need for comprehensive strategies to address unemployment and improve human resource quality.